2000
DOI: 10.1067/mpr.2000.107337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface treatments on shear bond strengths between a resin cement and an alumina core

Abstract: The use of Panavia 21 resin cement and a silane coupling agent can achieve a successful bond between either sandblasted or 5% HF acid-etched In-Ceram core material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 0 publications
1
43
0
11
Order By: Relevance
“…This would have been true for specimens that received airborne particle abrasion in relation to hydrofluoric acid etching, since the irregularities obtained by the acid are deeper, thus better protecting the resin-luting agent from the degradation process. 21 Even though some researchers 15,18,20 have shown that In Ceram Alumina is not altered by hydrofluoric acid and that this treatment is not enough to promote any difference in bond strength, the current results showed that the micro-shear bond strength was increased after this treatment. The shallow irregularities observed in the control group were also found after hydrofluoric acid etching.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This would have been true for specimens that received airborne particle abrasion in relation to hydrofluoric acid etching, since the irregularities obtained by the acid are deeper, thus better protecting the resin-luting agent from the degradation process. 21 Even though some researchers 15,18,20 have shown that In Ceram Alumina is not altered by hydrofluoric acid and that this treatment is not enough to promote any difference in bond strength, the current results showed that the micro-shear bond strength was increased after this treatment. The shallow irregularities observed in the control group were also found after hydrofluoric acid etching.…”
Section: Discussionmentioning
confidence: 54%
“…The morphological pattern obtained with 50-µm aluminum oxide particles was more effective for micromechanical bonding compared to airborne particle abrasion with 100-µm aluminum oxide particles, according to the findings that are consistent with other studies. [15][16][17][18][19][20][21] Using 9.5% hydrofluoric acid etching changed the surface topography of IPS Empress 2 and Cergogold ceramics, creating a topography similar to a honeycomb for Cergogold ( Figure 4C) and elongated the crystals with shallow irregularities for IPS Empress 2 ( Figure 3C). The chemical-etching process can be explained by the preferential reaction of hydrofluoric acid with the silica phase of the feldspathic ceramic to form hexafluorosilicates, which are removed by rinsing with water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramics with high crystalline content (aluminum and/ or zirconium oxides), also called acid-resistant ceramics, have demonstrated better clinical performance than feldspar-, leucite-, and lithium disilicate-based ceramics, known as acidsensitive ceramics. However, an increase in mechanical strength, by increasing the crystalline content and decreasing the glass content, results in an acid-resistant ceramic whereby any type of acid treatment produces insufficient surface changes for adequate bonding to resin 24,25,30,31,35,37,51,54,73 . For these acid-resistant ceramics, a silica coating process (silicatization) has been suggested to maximize the bond to resin 30,42,51,54,70,75 .…”
Section: Effect Of Surface Treatment On the Contact Angle And Work Ofmentioning
confidence: 99%
“…However, an increase in mechanical strength, by increasing the crystalline content and decreasing the glass content, results in an acid-resistant ceramic whereby any type of acid treatment produces insufficient surface changes for adequate bonding to resin 24,25,30,31,35,37,51,54,73 . For these acid-resistant ceramics, a silica coating process (silicatization) has been suggested to maximize the bond to resin 30,42,51,54,70,75 . The silica coating systems (Rocatec and Cojet, 3M-ESPE) create a silica layer on the ceramic surface because of the high-speed surface impact of the alumina particles modified by silica.…”
Section: Effect Of Surface Treatment On the Contact Angle And Work Ofmentioning
confidence: 99%